I can see myself in them, but they are not me”: Asian Boys’ Love (BL) drama and gay male viewers - Collin, Jerome; Ahmad Junaidy, Ahmad Hadzmy; Ting, Su Hie (MDPI, 2022)
Recent years have witnessed significant growth in research on the phenomenon of Asian Boys’ Love (BL) dramas, a new entertainment genre that features male characters who engage in same-sex love relations. However, much of this research has focused on, among others, heterosexual female viewers in terms of their knowledge of BL and their consumption patterns and motives. The present study aims at addressing this knowledge gap by gathering the views of gay male viewers regarding the BL that holds a place in their lives. In-depth interviews were conducted with six gay-identified participants living in Malaysia, with the study informed and guided by the framework of audience uses and appropriations of BL, and with the data collected and analyzed following the interpretative phenomenological approach (IPA) procedures. The findings revealed, on the one hand, polarized consumption patterns and, on the other hand, homogeneous motives, and reasons for consuming BL, including pure escapism, self-identification, and pure entertainment. The findings also revealed the participants’ views on whether the BL drama represented their identity and the real-life struggles of being a gay man in a country where homosexuality is still condemned and made illegal. These findings have implications that are relevant to the discussion of the role of the homoerotic media as a source of identity and livelihood among gay men.